EST(T): Should and Can Tax Performance be a Factor in Evaluating the Ethical, Moral and Social Performance of Corporations? - Allen, Christina; Krever, Richard (Australian School of Business, University of New South Wales, 2024)
Advocates for greater social responsibility by corporations who support corporate social responsibility or environmental, social and governance standards accounting by large companies increasingly call for tax behaviour to be considered one indicator of desired social behaviour. This advocacy may be based on naivety or a failure to understand the basis of tax avoidance by multinational enterprises. The decision by developed nations to allocate profits of multinational enterprises on the basis of notional arm’s length prices effectively endorses and invites companies to shift profits through transfer prices. Since the transactions in question would almost never take place between unrelated companies in a genuine arm’s length environment, there can be no comparable for developing an arm’s length price. As a result, the law effectively gives companies free rein to nominate arm’s length prices that are inherently fictional given the absence of similar transactions outside multinational enterprises. It can be argued, therefore, that it is both unfair and counterproductive to judge companies poorly because they follow the law and accept the invitation inherent in the arm’s length system to shift profits and avoid tax. If social responsibility advocates are concerned about tax avoidance by multinational enterprises, they should shift their attention from law-abiding companies to the legislatures and press for replacement of the system for allocating international profits to one that attributes profits to their actual sources based on objective indicators, not an allocation using fictional prices nominated by the companies shifting profits to low-tax jurisdictions.